METABOLIC SINGLE-PHOTON EMISSION COMPUTED TOMOGRAPHY WITH THE NEW RADIOPHARMACEUTICAL ⁹⁹ᵐTc-1-thio-D-glucose IN THE DIAGNOSIS AND MONITORING OF THE PRIMARY BREAST LYMPHOMA (CASE REPORT) - Ye. A. Dudnikova; V. I. Chernov; A. V. Muravleva; T. L. Kravchuk; R. V. Zelchan; A. A. Medvedeva; O. D. Bragina; Ye. L. Simolina; N. O. Popova; V. V. Vysockaja; N. M. Lukina; V. A. Shatalova; et al. (Сибирский онкологический журнал, 2020)
The article shows the feasibility of detecting and monitoring primary breast diffuse large B-cell lymphoma using single-photon emission computed tomography (SPECT) with 99mTc-1-thio-D-glucose (99mТс-TG), a new radiopharmaceutical. The innovative radiopharmaceutical makes it possible to evaluate the metabolism of tumor tissue without using positron emission tomography. The findings of 99mTc-TG SPECT obtained during diagnosis and monitoring of the patient were confirmed by the results of computed tomography. A comprehensive examination of the patient, including 99mTc-TG SPECT, made it possible to diagnose a rare case of primary breast lymphoma. Primary breast lymphoma accounts for 1.7–2.2 % of all extranodal nonHodgkin lymphomas. Diffuse large B-cell lymphoma is the most common histological type occurring usually as a unilateral palpable tumor in middle-aged women. Extranodal lymphomas account for less than 0.5 % of all malignant neoplasms of the breast. After 6 courses of immunochemotherapy, the patient underwent 99mTc-TG SPECT, which demonstrated persistent hypermetabolic activity in the breast. The patient received radiation therapy to the remaining tumor of the left breast. The patient is in remission and followed up at the Cancer Research Institute of Tomsk National Research Medical Center. Thus, 99mTc-TG SPECT is believed to be a promising method for visualizing primary breast lymphomas and assessing their treatment outcomes. It is an alternative to the standard approach using 18F-FDG positron emission tomography. The method compares favorably with positron emission tomography with its wide availability and low cost of study.